Metodologi Tafsir Ulama Nusantara di Tanah Pasundan (Telaah Atas Kitab Tafsir Rawdhat Al-‘Irfân dan Malja’ At-Thâlibîn Karya KH. Ahmad Sanusi) - Dedi Kuswandi; Abu Maskur (Jurnal test, 2022)
This paper discusses the methodology used by K.H. Ahmad Sanusi (1888-1950) in his interpretation of Rawdhat al-'Irfân and Malja' at-Thâlibîn and his answer to the Islamic religious polemic in Priangan in the 1930s. The book of interpretations of Rawdhat al-'Irfân and Malja' at-Thâlibîn is an interpretation of the Qur'an in Sundanese with pegon script. Ahmad Sanusi gives a characteristic Sundanese style in his interpretation as well as his critical response to the ideological competition between modernist and traditional Islam. His position has never been separated from the ranks of the Sunni Islamic tradition which tends to be more flexible in understanding the local traditions of the archipelago. This paper uses the method of analytical description of two books of interpretation by scholars of the archipelago so that it is hoped that this writing can give fresh air and introduce interpretations in Sundanese Tatar with Pegon script. It is concluded that the methodology of the two books of commentary Rawdhat al-'Irfân and Malja' at-Thâlibîn has differences, including (1) Tafsir Rawdhat al-'Irfân uses bi ra'yi interpretation which is based on the ijtihad mufassirnya and makes reason as the main way in interpreting the Qur'an while Tafsir Malja' at-Thâlibîn uses the interpretation of bi matsur (tafsir History) although in some places it does not prevent Sanusi from connecting his interpretation with the socio-religious background of his time; (2) in terms of method, the book of Tafsir Rawdhat al-'Irfân uses the ijmali method which tends to be presented globally, while the interpretation of Malja' at-Thâlibîn uses the tahlili method; (3) in terms of style, the interpretation of Rawdhat al-'Irfân places more emphasis on fiqh, while the interpretation of Malja' at-Thâlibîn tends to be more inclined to the teachings of the Sunnah Wal Jama'ah scholars, both in terms of Fiqh, theology and Sufism.